Endogenous Property Rights in a Hold up-Experiment - Mathias Erlei; J. Philipp Siemer (Technische Universität Clausthal, Abteilung für Volkswirtschaftslehre, 2004)
In a hold-up experiment designed to test theoretical predictions following from Hart (1995) and deMeza/Lockwood (1998) regarding investment behavior Sonnemans et al. (2001) (SOS) find only a partial confirmation of theory. According to SOS these deviations from standard theory can be explained by positive reciprocal behavior. In this paper, we replicate the experiment by SOS and add another group of treatments in which asset ownership is endogenized by auctioning off the assets. Our experiment shows that the results by SOS crucially depend on the ownership structure being exogenously assigned by the experimenter. We present experimental evidence that, by and large, corroborates the theoretical predictions made by Hart (1995).
Keywords: 330; property rights; hold-up; experiment; endogenous ownership structure